Zoulikha Bouabdellah, Visual Art, and Contemporary Calligraphy in Modern Algeria - Rahman, Suranta Abdul (UI Scholars Hub, 2019)
This study discusses the development of traditional poles that influence modern visual arts based on Aljazair culture, from conservative cultures under Ottoman influence to become Liberals after the French colonization brought to the Modern era. The majority of previous studies only discussed descriptive art variations in Algerian culture or only included elements of art in Algeria. This study uses qualitative methods, data collected by in-depth interviews with Visual Art experts at the best institutions in Indonesia and literature studies on art and culture in Algeria. This paper does not encourage artists to violate Islamic rules in their work. However, this study shows that there are artists who come out of Islamic rules to achieve certain goals and are not taboo in art. The paper concludes that a religious concept that is applied in a state principle does not make and guarantee that all members of the entire community line are fully conservative and obedient to the conservative rules in the state or legilation that must be obeyed in that country.